PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI POWTOON MATERI SANGGUL EVENING STYLE PADA SISWA KELAS XI SMKN 2 JOMBANG - Shella Oktavia Ronita; Novia Restu Windayani; Sri Dwiyanti; M.A. Hanny Ferry Fernanda (Program Studi Pendidikan Tata Rias, 2025)
Learning media has an important function in learning, namely as an effective tool for students and can be used for independent learning. The purpose of the study was to determine the feasibility, development results, and student responses regarding powtoon animated video media on evening style bun styling material.This type of research is research and development (R&D) with the ADDIE approach.The results of the overall learning media validation assessment obtained an average of 4.65 so that based on the media feasibility criteria it was stated that the learning media developed was “very feasible”. The overall data of the student response questionnaire obtained an average respondent's answer of 4.44 so that based on the response criteria table the results of the student questionnaire are included in the criteria “very good” The powtoon animated video-based learning media for evening style bun material developed proved to be very feasible by looking at the results of the students' responses which were included in the very good qualifications, so it is possible that the learning media can be used on an ongoing basis at SMKN 2 Jombang.Keywords: Animated videos Powtoon, sanggul evening style